Educative Web-Based Virtual as a Learning Media For Training Scientific Attitude In High School Student - Haka, Nukhbatul Bidayati; Sari, Maycha Erliana; Masya, Hardiyansyah; Rakhmawati, Ismi (Phenomenon : Jurnal Pendidikan MIPA, 2024)
Media is important in learning, especially with the development of science and technology. This study aims to design and develop a virtual laboratory based on web education as a learning media and to train the scientific attitudes of high school students. The type of research used in Research and Development (R&D) refers to the nine stages of Borg and Gall. The feasibility test of web education uses a validation questionnaire of material experts, language experts, media experts, and educator response questionnaires. The study results showed that material experts comprised 87.5%, language experts comprised 94%, media experts comprised 91.5%, and educator response questionnaires comprised 85.33%. So, web-educative biology is a very feasible category. The effectiveness of the media in training scientific attitudes is known to have an average n-gain value of 0.59 (moderate) for the experimental class and 0.39 (moderate) for the control class. Based on the results of the t-independent test, a sig of 0.00 <α value (0.05) was obtained, which means that H1 is accepted and H0 is rejected. It is concluded that the web-based educational Virtual Laboratory is effective in training the scientific attitudes of high school students and is suitable for use as a biology learning medium.